Disabling Lee Kuan Yew and the Singapore Story: The Problematic Logics of Inclusion in Contemporary Singapore. Issue 2 (3rd April 2023) - Zhuang, Kuansong Victor
ABSTRACT: Representations of Lee since his passing have focused on discussing the role that he played in building Singapore and the politics of remembering him. This article takes a different approach, underpinned by developments towards the incorporation of disabled people in life both in Singapore and internationally. Embracing disability as a valid form of embodiment as well as an important source of critical knowledge, this article uses a disability analytic to disable both the figure of Lee Kuan Yew and the Singapore Story. It does so to expose the underpinning logics and contradictions surrounding disability, which affords opportunities to reimagine a more inclusive Singapore.